WORK-LIFE BALANCE, COMPENSATION, AND JOB SATISFACTION AS DRIVERS OF EMPLOYEE RETENTION IN STATE-OWNED ENTERPRISES - Susati, Evi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Employee retention remains a critical challenge for state-owned enterprises (SOEs), necessitating a deeper understanding of the factors that influence employees' decisions to stay within an organization. This study examines the impact of work-life balance, compensation, and job satisfaction on employee retention, with job satisfaction analyzed as a mediating variable. Using a quantitative approach, data were collected from SOE employees and analyzed through descriptive statistics, correlation analysis, regression modeling, and mediation analysis. The findings indicate that all three factors significantly contribute to employee retention, with job satisfaction emerging as the strongest predictor. Furthermore, job satisfaction partially mediates the relationship between work-life balance, compensation, and retention, highlighting its central role in workforce stability. These results suggest that organizations should prioritize initiatives aimed at enhancing job satisfaction through career growth opportunities, recognition programs, and supportive work environments. Additionally, fostering a healthy work-life balance and offering competitive compensation packages are essential strategies for improving employee retention. The study provides valuable insights for HR practitioners and policymakers in SOEs to develop effective retention strategies. Future research should explore additional variables, such as leadership styles and organizational culture, to gain a more comprehensive understanding of employee retention dynamics.